Degree of Needs’ Importance and Satisfaction Among Caregivers of Children with Cancer in Jordanian Families - Alaedein, Jehad (Jordan Journal of Educational Sciences, 2012)
The aim of this study is to identify the degree of importance and satisfaction of caregiving needs among family members who have children with cancer in Jordan. A purposive sample (N=100) of family caregivers participated in this study, (80%) of them are females. The participating caregivers were recruited and interviewed in a medical center located in Amman. Results showed that needs of obtaining information, and accompanying the sick child, scored the highest levels of importance and satisfaction, while need of facilitating the development of the sick child scored the lowest levels of importance and satisfaction among caregivers. Stepwise regression analyses’ findings also showed that degree of satisfaction with needs of negotiating with health care professionals, maintaining the caregiver’s own strength, and accompanying the sick child were the best significant predictors of the total degree of caregiving needs’ importance. Moreover, the results showed that the group of family caregivers at the diagnostic stage tended to be significantly less satisfied with the needs of obtaining information than those at the treatment stage. In addition, those who mentioned their need for psychological help were significantly less satisfied with the needs of maintaining the caregiver’s own strength, facilitating the development of the sick child and obtaining information than those who did not mention their need for such a help. The study includes counseling implications and interventions.